JAMAAH MAIYAH MOCOPAT BENEFITS: COUNTER CULTURE - Annissa Valentina (Universitas Nahdlatul Ulama Lampung, 2019)
Many social movements in Indonesian carry out about social change, but those have not bring changing of mind value level into the reality. It is unique when any different social movement present with opposing the inrelevant ongoing tradition, and developing the new alternative for making a change that called by counter culture. This counter culture movement is referred by Jamaah Maiyah Mocopat Syafaat. This social movement referred as counter culture for youth that different with general ones, and show its unique in opposing the ongoing “tradition/culture” with establishing the new ones. Because the old ones is inrelevant or deviate. Jamaah Gerakan Mocopat Syafaat theoretically comply counter culture criteria, they are possessing similar views; doing resistance; and striving also establishing humanity values that show the indicate to public the properness of this social movements as counter culture for youth.